Application of Word Square Media in Strengthen Arabic Vocabulary Memorization at Madrasah Ibtidaiyah Fifth Grade - Muhammad Sufyan Ats-Tsauri; Laini Azizah Hasani (Yayasan Zia Salsabila, 2026)
Arabic language learning at the madrasah ibtidaiyah level still faces various challenges, particularly in students’ low mastery of vocabulary (mufradat). This condition is influenced using conventional teaching methods and the limited utilization of innovative and engaging learning media, resulting in low student motivation and learning outcomes. Therefore, it is necessary to implement effective learning strategies using interactive media. This study aims to analyze the application of Word Square media and its effectiveness in improving Arabic vocabulary memorization among fifth-grade students at Madrasah Ibtidaiyah Maklumul Mukminin NW Pondok Gedang in the 2025/2026 academic year. This research employed a qualitative approach with a descriptive design to explore the learning process in depth. Data were collected through classroom observations, interviews with teachers and students, and documentation. Data analysis was conducted using the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. The validity of the data was ensured through triangulation techniques and credibility checks. The findings reveal that the implementation of Word Square media significantly improves student engagement, motivation, and participation in learning activities. The learning process becomes more interactive and enjoyable through word-search activities that involve visual and kinesthetic elements. Furthermore, students’ vocabulary memorization ability shows a notable improvement, indicated by the increase in average scores from below 70 to approximately 90, as well as a significant reduction in the number of low-achieving students. In conclusion, Word Square media is an effective and innovative learning tool that enhances both cognitive and affective aspects of Arabic language learning, particularly in improving vocabulary memorization at the elementary level.